Treatment of endometrioma for improving fertility. (February 2017) - Leone Roberti Maggiore, Umberto; Gupta, Janesh Kumar; Ferrero, Simone
Abstract: Endometrioma is a frequent clinical manifestation of endometriosis. It is controversial how endometriomas may affect women's fertility. This review addresses: the impact of the endometrioma per se and of its surgical treatment on ovarian physiology, on the ovarian reserve, on spontaneous conception and pregnancy outcomes, and on IVF/ICSI outcomes. Based on current evidence, although there are plausible biological detrimental effects on the ovarian cortex surrounding the endometrioma and an impairment of the normal ovarian physiology, the clinical impact of the endometrioma per se is not significantly altered. There is a negligible detrimental effect on ovarian reserve with spontaneous ovulation not being impaired. Conversely, surgical excision of an endometrioma reduces ovarian reserve as measured by AMH levels. Studies investigating the impact of the endometrioma per se and of its surgical treatment in women requiring IVF/ICSI show similar implantation rates, clinical pregnancy rates and live birth rates between women with endometrioma and controls.